Perilaku Masyarakat dalam Mengelola Sampah di Kota Bima Nusa Tenggara Barat - Darmawan, Awan (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Urban waste become big problem some cities in Indonesia not only large cities, even Bima city. The question is how the community behavior in managing the waste in Bima City NTB. Research using quantitative approach with descriptive methods, analysis techniques using frequency distribution. Data collection through interviews with government using purposive sampling, the questionnaires to the public using simple random sampling. The research results showed the majority of community behavior as solid waste in containers, community behavior in waste separation has not been done, community behavior in provision of garbage containers has been done, community behavior in transport of garbage and trash culling by the janitor, some destroy by burning and washed in the river, and the behavior of people who throw litter due to unavailability of landfills. The recommended to improve peopleâ€™s Â behavior with training and empowerment people to manage waste, the provision of containers near from the settlement, manufacture of pilot projects to stimulate public motivation, rulemaking area of waste management, and differentiate waste transportation schedules of organic and inorganic.